Key technologies and equipment for green short process of coal mine drainage resource utilization - Xuwen HE; Shaozhou WANG; Xuewei ZHANG; Xiaoqing JI (Meitan xuebao, 2024)
Coal is an important industrial raw material in China, closely related to its economic development. During coal mining, a large amount of coal mine drainage is generated, which is an important unconventional water resource that needs to be properly treated. However, the existing coal mine drainage treatment technology generally has problems such as large land occupation, long process, dosing requirement, complex operation and maintenance, and unstable effluent quality. In order to shorten the treatment process, improve treatment efficiency, and ensure effluent quality, it is urgent to develop new key technologies and equipment. This study adopts the PolyCera membrane direct filtration technology to treat coal mine drainage. By comparing and analyzing the conditions of membrane flux, membrane specific flux, operating pressure, and circulating flow rate, the optimal operating parameters are determined as follows: operating pressure of 0.2 MPa, circulating flow rate of 18 m3/ h. The treatment process does not require dosing, and the stable concentration of suspended solids in the effluent is less than 1 mg/L, and the stable turbidity is less than 1 NTU. Using the most widely used membrane fouling model to explore the mechanism of membrane fouling, the analysis results of membrane fouling indicate that membrane fouling is mainly caused by cake layer fouling, accompanied by intermediate fouling, specifically manifested as surface fouling of the membrane and blockage of membrane pores. The membrane surface pollution is timely removed through hydraulic backwashing, with an optimal backwashing time of 60 s and a flux recovery rate of 85.12%. By regularly cleaning the membrane pores with chemical cleaning, and with a composite formulation for 3 hours cleaning, the flux recovery rate can reach over 95%. Engineering cases have shown that the PolyCera membrane direct filtration can directly replace the "coagulating sedimentation -filtration-ultrafiltration" (one process replaces three), and has been continuously and stably operating for 2 years, meeting the design water production requirements. The system recovery rate is above 90%, and the water quality meets the requirements of 24 standard limits for Class III surface water environmental quality in GB 3838—2002. Also, it has a high degree of automation and can be unmanned, achieving some new requirements of resource utilization of coal mine drainage, green and short process, energy conservation, efficiency, and intelligence. It can provide a technical reference for the large-scale promotion and application of the technology.